Characterization of the hormone-binding domain of the chicken c-erbA/thyroid hormone receptor protein. - Muñoz, A (1988)
To identify and characterize the hormone-binding domain of the thyroid hormone receptor, we analyzed the ligand-binding capacities of proteins representing chimeras between the normal receptor and P75gag-v-erbA, the retrovirus-encoded form deficient in binding ligand. Our results show that several mutations present in the carboxy-terminal half of P75gag-v-erbA co-operate in abolishing hormone binding, and that the ligand-binding domain resides in a position analogous to that of steroid receptors. Furthermore, a point mutation that is located between the putative DNA and ligand-binding domains of P75gag-v-erbA and that renders it biologically inactive fails to affect hormone binding by the c-erbA protein. These results suggest that the mutation changed the ability of P75gag-v-erbA to affect transcription since it also had no effect on DNA binding. Our data also suggest that hormone-independent activity of P75gag-v-erbA provided a selective advantage to the avian erythroblastosis virus during the original selection for a highly oncogenic strain of the virus.